Evaluasi EVALUASI PENGARUH FAKTOR PELAYANAN, FASILITAS, DAN KEAMANAN PENERBANGAN DALAM MENINGKATKAN KEPUASAN PENUMPANG DI BANDARA: Faktor Pelayanan, Fasilitas, dan Keamanan Penerbangan berdampak pada kepuasan penumpang - Misbah Sudur; Pamuraharjo, Hemi (Yayasan Nuraini Ibrahim Mandiri, 2024)
This study aims to analyze the effect of services, facilities, and flight security on passenger satisfaction at airports. The quality of service, completeness of facilities, and flight safety assurance are important factors that can affect the level of passenger satisfaction. The method used in this research uses quantitative methods with a focus on literature studies to examine in depth the related theories and investigate the relationship and impact of the main variables in the study. The results showed that service, facilities, and flight security simultaneously had a positive and significant effect on passenger satisfaction with different percentage figures depending on the context and location of the airport concerned. Improving service quality, providing adequate facilities, and improving flight security need to be continuously pursued by airport managers to achieve optimal satisfaction for passengers. This research contributes as input for the development of airports that are oriented towards customer satisfaction. Keywords: services, facilities, flight security, passenger satisfaction, airports